In vitro biocompatibility of the novel ceramic composite baghdadite for defect augmentation in revision total hip arthroplasty - Jaenisch, Max; Guder, Christian; Ossendorff, Robert; Randau, Thomas M.; Gravius, Sascha; Wirtz, Dieter C.; Strauss, Andreas C.; Schildberg, Frank A. (Journal of Functional Biomaterials, 2023)
Biological augmentation of bony defects in weight-bearing areas of both the acetabulum and the femur remains challenging. The calcium-silicate-based ceramic Baghdadite is a very interesting material to be used in the field of revision total hip arthroplasty for the treatment of bony defects in weight-bearing and non-weight-bearing areas alike. The aim of this study was to investigate the biocompatibility of Baghdadite utilizing an osteoblast-like, human osteosarcoma cell line (MG-63) and the human monocytic leukemia-derived cell line (THP-1). THP-1-derived macrophages and MG-63 were indirectly exposed to Baghdadite for 7 days using a transwell system. Viability was assessed with MTT assay and pH analysis. To investigate proliferation rate, both cell lines were labelled using CFSE and flow cytometrically analyzed. ELISA was used to measure the secretion of IL-1ß, IL-6 and TNFα. The investigation of viability, while showing a slight difference in optical density for the MTT assays in MG-63 cells, did not present a meaningful difference between groups for both cell lines. The comparison of pH and the proportion of living cells between groups did not present with a significant difference for both THP-1 and MG-63. Baghdadite did not have a relevant impact on the proliferation rate of the investigated cell lines. Mean fluorescence intensity was calculated between groups with no significant difference. Baghdadite exerted a proinflammatory effect, which could be seen in an upregulated production of TNFα in macrophages. Production of IL-1ß and IL-6 was not statistically significant, but the IL-6 ELISA showed a trend to an upregulated production as well. A similar effect on MG-63 was not observed. No relevant cytotoxicity of Baghdadite ceramics was encountered. Baghdadite ceramics exhibit a proinflammatory potential by significantly increasing the secretion of TNFα in THP-1-derived macrophages. Whether this proinflammatory potential results in a clinically relevant effect on osteointegration is unclear and requires further investigation. Baghdadite ceramics provide an interesting alternative to conventional bone substitutes and should be further investigated in a biomechanical and in vivo setting.
Gesehen am 16.09.2024